Quality Assurance Islamic Perspective: an Alternative in Islamic-Based Public Education Institutions - Nurjaman, Ujang; Al Mighwar, Muhammad; Harun, Makmur; Mu'min, U. Abdullah; Syaie, Akmad Najibul Khairi (Cendekia: Kependidikan dan Kemasyarakatan, 2022)
This study aims to investigate the quality assurance according to Islam and the experience of its application in Islamic-based public education institutions. Quality assurance in education and other fields has been widely practiced in Indonesia. Many experts have discussed quality assurance, but it is still in education in general, not specifically religious education. However, it is still in the aspect of education generally, not specifically religious education. Religious education has a strategic and urgent role in instilling morals/noble character in the generation of the Indonesian nation. Therefore, Islamic religious education is given special attention in the 2013 curriculum and given additional hours of study to produce a generation of people who are moral, faithful, and pious. It is said that the better generation, the better the quality assurance of education. This research was a qualitative study. It was a case study. It was at Vocational High Schools Ma'arif Nahdhatul Ulama, Garut, West Java, Indonesia (SMK Ma'arif NU Garut). This study shows that the application of quality assurance in Islam must balance the religious and rationality values so that there is no paradox between the two, as was successfully implemented at SMK Ma'arif NU Garut. This success proves that no religious values contradict rationality, so it should be used as a basis to support or complement the theory/concept and practice of quality assurance in other Islamic-based public education institutions.